A Phenomenological Mathematical Modelling Framework for the Degradation of Bioresorbable Composites - Moreno-Gomez, Ismael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents a generalised computational model for the degradation of resorbable composites, using analytic expressions to represent the interwoven phenomena present during degradation. It then combines this modelling framework with a comprehensive database of quantitative degradation data mined from existing literature and from novel experiments, to provide new insights into the interrelated factors controlling degradation. Resorbable composites made of biodegradable polyesters and calcium-based ceramics have significant therapeutic potential as tissue engineering scaffolds, as temporary implants and as drug-loaded matrices for controlled release. However, their degradation is complex and the rate of resorption depends on multiple connected factors such as the shape and size of the device, polymer chemistry and molecular weight, particle phase, size, volume fraction, distribution and pH-dependent dissolution properties. Understanding and ultimately predicting the degradation of resorbable composites is of central importance if we are to fully unlock the promise of these materials.
Introduction -- Literature review -- Degradation of bioresorbable composites: the models -- Degradation of bioresorbable composites: tricalcium phosphate case studies -- Degradation of bioresorbable composites: hydroxyapatite case studies -- Experimental degradation study of PLGA-CaCO3 nanocomposites -- Degradation of bioresorbable composites: calcium carbonate case studies -- Conclusions and future work -- Appendix.
Keywords: Biomaterials; Mathematical physics; Materials -- Analysis; Biomaterials; Theoretical, Mathematical and Computational Physics; Characterization and Analytical Technique